An Evaluation of English Program at Pesantren Ali Maksum - Syaiful Mujab; Yuyun Yulia (Universitas Sarjanawiyata Tamansiswa, 2018)
This research is aimed at describing the implementation of English program at Pesantren Ali Maksum in terms of the Community Language Learning, and reveal the strengths and weaknesses of English program in English teaching and learning process in Pesantren Ali Maksum in terms of Community Language Learning (CLL).This research is an evaluation research employing CLL model by Larsen-Freeman (2000) and Richard-Rodger (2003). The data were collected through in-depth interviews, observation and document analysis. The data were analyzed using Miles, Huberman and Saldana’s flow model of qualitative data research which included data collection, data condensation, data display and conclusion drawing.The implementation of English program indicates that English program has been generally well-conducted through six characteristics and eight activities although from some parts need to be improved or changed such as in Larsen-Freeman characteristics. Aggression item the tutor needs to keep a distance to junior students to avoid disrespectful. Richard-Rodger activities term has been well-implemented through eight activities some needs improvement and change. Translation term, the tutor needs training. Group work and listening terms need a change in managing the place in order to avoid disturbance each group.